1994
DOI: 10.1139/p94-112
|View full text |Cite
|
Sign up to set email alerts
|

The B′ 1Σu+ → X1Σg+ and D1Πu → X1Σg+ band systems of molecular hydrogen

Abstract: Spectral line positions and emission probabilities of the B′ 1Σu+ → X 1Σg+ and D 1Πu → X 1Σg+ band systems of molecular hydrogen have been calculated by solving a system of four coupled Schrödinger equations. A great number of rotational lines, emitted by a low-pressure electric discharge in H2, have been identified from 122 nm down to 78 nm. All the 69 bands of the B′ 1Σu+ → X 1Σg+ system and many high-J lines of 145 bands of the D 1Πu → X 1Σg+ system are reported for the first time. Improved molecular consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 0 publications
11
97
1
Order By: Relevance
“…The origin of the velocity scale for this figure and all following ones is defined at the position of the CO-bearing component at z abs = 2.68957. and oscillator strengths were taken from Morton & Noreau (1994) and Eidelsberg & Rostas (2003) for CO and from Abgrall & Roueff (2006) for HD. Updated wavelengths of H 2 Lyman and Werner bands were taken from Bailly et al (2010), with oscillator strengths from the Meudon group 1 , based on calculations described in Abgrall et al (1994). Photospheric solar abundances are taken from Asplund et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the velocity scale for this figure and all following ones is defined at the position of the CO-bearing component at z abs = 2.68957. and oscillator strengths were taken from Morton & Noreau (1994) and Eidelsberg & Rostas (2003) for CO and from Abgrall & Roueff (2006) for HD. Updated wavelengths of H 2 Lyman and Werner bands were taken from Bailly et al (2010), with oscillator strengths from the Meudon group 1 , based on calculations described in Abgrall et al (1994). Photospheric solar abundances are taken from Asplund et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…The FUSE spectrum at the (1, 0) vibrational transition was too noisy to perform a good fit. The H 2 line positions and oscillator strengths were adopted from Abgrall et al (1994). The total transition probabilities that include the transitions to continuum (dissociating) states were taken from Abgrall et al (2000).…”
Section: Column Densitiesmentioning
confidence: 99%
“…It should be noted that most of these 40 lines are resonance transitions. The optical thickness in the discharge experiments of Roncin et al (1984), Abgrall et al (1994), and prevents these resonance transitions from being observed. It should also be pointed out that the previous high-resolution emission studies were limited to wavelengths longer than 786 presumably since A , the weakness of the transitions and the required optical thickness make it impractical to study the transitions on the blue side of 786…”
Section: Methodsmentioning
confidence: 96%
“…While molecular hydrogen has been investigated extensively in the extreme ultraviolet (EUV) region with photoabsorption (MonÐls 1961(MonÐls , 1965Namioka 1964aNamioka , 1964bWilkinson 1968 ;Takezawa 1970 ;Herzberg & Jungen 1972 ;Dabrowski 1984 ;Glass-Maujean, Breton, & Guyon 1984, 1985, photoionization (Demher & Chupka 1976, 1995, and nonlinear laser techniques Pratt et al 1990Pratt et al , 1992Pratt et al , 1994OÏHalloran et al 1988OÏHalloran et al , 1989Hinnen et al 1994aHinnen et al , 1994b, 1996Reinhold, Hogervorst, & Ubachs 1996, 1997Hogervorst et al 1998), relatively few emission studies of H 2 have been performed in the EUV region (Herzberg & Howe 1959 ;Lunay, & Roncin 1980, 1985Daborwski Larzillie re, 1984 ;Roncin, Launay, & 1984 ;Ajello et al 1984, Larzillie re 1988Abgrall et al 1987Abgrall et al , 1994. To the blue side of the 1040 wavelength region, emissions from various levels of the A and Rydberg states to the 1sp g npp u 1& u 1sp g npn u 1% u v i \ level of the X state (i.e., resonance transitions) domi-0 1& g nate the spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation